2015
DOI: 10.1084/jem.20141731
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Plasmodium in reticulocytes can occur without hemozoin formation, resulting in chloroquine resistance

Abstract: Lin et al. generate Plasmodium berghei mutants lacking enzymes critical to hemoglobin digestion. A double gene deletion mutant lacking enzymes involved in the initial steps of hemoglobin proteolysis is able to replicate inside reticulocytes of infected mice with limited hemoglobin degradation and no hemozoin formation, and moreover, is resistant to the antimalarial drug chloroquine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 34 publications
5
85
0
Order By: Relevance
“…For this we used a gene-deletion mutant for the dipeptidyl peptidase 3 (DPAP3), Δ dpap3 28. Infection with 10 5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this we used a gene-deletion mutant for the dipeptidyl peptidase 3 (DPAP3), Δ dpap3 28. Infection with 10 5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…have shown that heme is responsible for artemisinins’ activation to react and conjugate with many cellular proteins. Nevertheless, Khan’s group has reported that replication of Plasmodium in reticulocytes can occur without hemozoin formation, resulting in chloroquine resistance, but their sensitivity to artesunate, an artemisinin derivative, also thought to be dependent on hemoglobin degradation, is retained36.…”
Section: Discussionmentioning
confidence: 99%
“…2015). Hemoglobin degradation in the parasite takes place within the digestive vacuole (also referred to as the food vacuole), a lysosome-like organelle containing enzymes that break down hemoglobin and convert heme, a toxic catabolite, into non-toxic hemozoin (Goldberg 2005).…”
Section: The Parasitophorous Vacuole and Parasitophorous Vacuole Membmentioning
confidence: 99%